Experimental Study on the Effect of the Geometry of Punching Tool on Clinch Joints - Jónás, Szabolcs; Kovács, Péter Zoltán (International Journal of Engineering and Management Sciences, 2020)
In this study the effect of the punching tool’s geometry on aluminum alloy clinch joints is analyzed by experiments. Based on FE simulations the tip radius and the cone angle of the punching tool is changed, and their effect was analyzed by microscopic investigations and single lap tensile-shear tests.